2015
DOI: 10.3945/ajcn.114.104976
|View full text |Cite
|
Sign up to set email alerts
|

Red meat, dairy, and insulin sensitivity: a randomized crossover intervention study

Abstract: Background: Epidemiologic studies have linked high consumption of red and processed meat with risk of developing type 2 diabetes, whereas high dairy consumption has been associated with decreased risk, but interventions have been limited. Objective: We compared the effects on insulin sensitivity of consuming a diet high in lean red meat with minimal dairy, a diet high in primarily low-fat dairy (from milk, yogurt, or custard) with no red meat, and a control diet that contained neither red meat nor dairy. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
(34 reference statements)
2
40
1
Order By: Relevance
“…The higher glucose response 30 min after consumption of the red meat meal may have been be attributable to a small difference in the glycemic load between the orange juice and the milk and yogurt or the type of sugar. An insulinotropic effect of dairy was not observed and could not account for the reduction in insulin sensitivity that we observed in our chronic feeding study (18). FIGURE 2 Mean 6 SEM postprandial glucose, insulin, and triglyceride concentrations after 2 isocaloric meals containing red meat (triangles) or dairy (circles) (n = 43).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The higher glucose response 30 min after consumption of the red meat meal may have been be attributable to a small difference in the glycemic load between the orange juice and the milk and yogurt or the type of sugar. An insulinotropic effect of dairy was not observed and could not account for the reduction in insulin sensitivity that we observed in our chronic feeding study (18). FIGURE 2 Mean 6 SEM postprandial glucose, insulin, and triglyceride concentrations after 2 isocaloric meals containing red meat (triangles) or dairy (circles) (n = 43).…”
Section: Discussionmentioning
confidence: 70%
“…Fasting glucose and insulin concentrations did not change in a comparison of two 5-wk weight-loss diets, one of which was high in lean red meat and one of which high in soy protein (16), whereas oily fish intake was shown to improve insulin sensitivity compared with the effect of red meat intake in an 8-wk crossover intervention (17). In contrast to epidemiologic evidence, our previous research showed that a 4-wk diet that was high in primarily low-fat dairy reduced insulin sensitivity compared with the effect of a diet high in lean red meat or no dairy (18).…”
Section: Introductionmentioning
confidence: 93%
“…It appears that 2.8 g whey in milk and yogurt of our dairy/chicken/nuts/wholegrain meal has no effect on postprandial glycemia and insulin secretion and that meat and dairy protein probably have equivalent effects on insulin release. As there are inconsistent effects of dairy consumption on insulin sensitivity [37,38] and few dairy interventions examining acute effects on glucose and insulin [34] exist, the possible explanation for overall effects observed in the dairy/chicken/nuts/wholegrain meal of this present study are not due to dairy but other meal components. Alteration in gut microbiota may play a role in the beneficial effects seen with the dairy/chicken/nuts/wholegrain diet [39].…”
Section: Discussionmentioning
confidence: 84%
“…We have illustrated that elevation of dietary protein intake using dairy products does not have a negative influence on insulin sensitivity. While some studies have linked increased consumption of red meat to the development of insulin resistance [42], recent data from longitudinal feeding studies dispute this assertion [43]. These findings indicate that reasonable elevations in protein intake do not alter glucose kinetics in subjects with metabolic syndrome, and also highlight the empirical nature of nature of epidemiological research [44].…”
Section: Discussionmentioning
confidence: 99%